2009
DOI: 10.1159/000209265
|View full text |Cite
|
Sign up to set email alerts
|

A Screening Instrument to Measure the Prevalence of Neurological Disability in Resource-Poor Settings

Abstract: Background: Very little is known about the prevalence of neurological morbidity in Africa. Much of this is due to the difficulty in performing epidemiological surveys in these settings. A screening instrument to measure neurological disease in resource-poor settings was designed by the World Health Organization in 1981, but several problems with it have subsequently been recognized. Methods: We created a new screening instrument that addressed problems with the original instrument identified by prior investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…This newly developed instrument had a Youden's index of 0.861 and specificity of 96%, which was higher than all other questionnaires; while, the WHO-recommended questionnaires [5,14] showed a higher sensitivity (95%) at a cost of lower specificity (60 and 72%). Our instrument also showed the highest ROC-AUC (0.977) compared to other instruments such as the SNES [4] (0.934), WHOmodified instrument [14] (0.933), and recommended index by Duarte et al [16] (0.947), Setthawatcharawanich et al [18] (0.950) and Chan et al [17] (0.968) to screen Parkinsonism. It is worth noting that all of these instruments were implemented and assessed on the same original database in which our newly screening questionnaire was developed from.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…This newly developed instrument had a Youden's index of 0.861 and specificity of 96%, which was higher than all other questionnaires; while, the WHO-recommended questionnaires [5,14] showed a higher sensitivity (95%) at a cost of lower specificity (60 and 72%). Our instrument also showed the highest ROC-AUC (0.977) compared to other instruments such as the SNES [4] (0.934), WHOmodified instrument [14] (0.933), and recommended index by Duarte et al [16] (0.947), Setthawatcharawanich et al [18] (0.950) and Chan et al [17] (0.968) to screen Parkinsonism. It is worth noting that all of these instruments were implemented and assessed on the same original database in which our newly screening questionnaire was developed from.…”
Section: Discussionmentioning
confidence: 88%
“…The content validity of different items in our instrument was also acceptable ranging from 0.74 to 0.81, while Setthawatcharawanich et al [18] showed a wider range (0.6-1.0) for their 4-item screening questionnaire. The number of selected items in our questionnaire (n = 6) is lower than some previously developed instruments such as the BHSQ [13] with 16 questions, the ones developed by Tanner et al [15] , Duarte et al [16] , and Sevillano et al [19] with 9 items and the WHO-modified tool [14] with 7 items. However, our instrument showed better diagnostic values, reliability and content validity.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The World Health Organisation has developed the STEPS programme for surveillance of stroke and vascular risk factors in lowand middle-income countries [6] , and in a recent issue of Neuroepidemiology, a screening instrument to measure the prevalence of neurological disability in resource-poor settings was presented [7] .…”
Section: Commentmentioning
confidence: 99%